Investigating language attitudes in Pakistani immigrant individuals of France - Shahzaman Haque (Educazione Interculturale, 2022)
This article attempts to investigate a case study on the language attitudes of Pakistani immigrants in France, drawing on the theoretical framework of family language policy. Over 37 individuals of Pakistani descent living in the suburbs of Paris participated in this study through a questionnaire on language attitudes. All the participants showed a positive attitude towards the teaching of the Urdu language to their children or to the second generation. Within the family arena, it has been observed that the consequences of prolonged language contact led to language changes (Ricento, 2006) from the heritage language (Punjabi in the case of the illustrated case study’s participants) to the language of prestige (Urdu) through verbal interaction with the second generation. This study also takes into account the linguistic biographies of some students of Pakistani origin enrolled in a Bachelor’s program with Urdu as major subject at the National Institute of Oriental Languages and Civilization in Paris. The reports by the students have further attested to language attitudes in favour of Urdu emerging as an important tool in the socio-educational context.